Verbal memory test performance in patients with bipolar I disorder attending a psychiatric clinic of a university hospital in Kuala Lumpur, Malaysia - Ibrahim, Normala; Abdul Rahman, Abdul Hamid; Shah, Shamsul Azhar (ASEAN Federation for Psychiatry and Mental Health, 2009)
Objective: The study aims to determine pattern of verbal memory and learning impairment and its associated factors among patients with bipolar I disorder in a psychiatric clinic of a university hospital.